An Analysis of the Tensile Strength of Spot Welded Joints in ST40 Low-Carbon Steel - Rahmat Hidayat; Mukhnizar Mukhnizar; Azmil Azman (The Future of Education Journal, 2026)
Spot welding is widely used in the automotive industry due to its fast process, efficiency, and neat joint results. However, the joint strength is highly influenced by welding parameters, especially pressing time. This study aims to determine the tensile strength of spot-welded joints on low-carbon steel ST40, analyze the effect of pressing time variations, and identify the optimum pressing time that produces the strongest joint. The results showed that a pressing time of 20 seconds produced the highest tensile strength of 36.69 MPa, yield strength of 205.56 MPa, and modulus of elasticity of 406.85 MPa. Therefore, a pressing time of 20 seconds is considered the optimum condition to produce strong spot-welded joints on ST40 steel.